Determination the Total Phenolic Contents in Some Foods Using Solid Phase Extraction - Al-Ameri, Salam Abbas Hasan; Al-Shemari, Muntadher Mohan Alwan (Al-Nahrain Journal of Science, 2018)
Solid phase extraction with Amberlite XAD-8 resin was used for the determination of total phenolic contents in some foods using Folin-Ciocaltue’s method and formation blue complex absorbance measured at λ max 765 nm. The effecting factors pH, time of extraction, number of the extraction batches and elution solvent was studied. The obtain results showed that the highest extraction occurs at optimal conditions, pH=2 at extraction time 10min. and using acetonitrile as elution solvent. The distribution coefficient Kd , for the adsorption and elution has been calculated for Gallic acid, 7-hydroxy coumarin. This resin prove to be capable for adsorption of these compound from aqueous samples, and acetonitrile was the supreme solvent for elution owing to superior polarity in addition to dielectric constant compare with ethanol and diethyl ether. The precision and accuracy of this method was found by analysis a laboratory made of Gallic acid samples, the statistical managements showed relative error ranged from ± 0.842 to 9.462%, mean error equal to -2.440, standard deviation 1.149, relative standard deviation not exceed 2.416%, and confidence limit 47.560±1.426. The effectively applied result of this method for determination of total phenolic contents in eight different type of food samples showed that the amount was varying from the highest value in dates which equal 10.466 mg GAE/10g sample and 1.160 mg GAE/10g sample in kiwi as lowest value.